Exploring a novel environment improves motivation and promotes recall of words - Schomaker, Judith; van Bronkhorst, Marthe L. V.; Meeter, Martijn (Frontiers in Psychology, 2014)
Active exploration of novel environments is known to increase plasticity in animals, promoting long-term potentiation in the hippocampus and enhancing memory formation. These effects can occur during as well as after exploration. In humans novelty’s effects on memory have been investigated with other methods, but never in an active exploration paradigm. We therefore investigated whether active spatial exploration of a novel compared to a previously familiarized virtual environment promotes performance on an unrelated word learning task. Exploration of the novel environment enhanced recall, generally thought to be hippocampus-dependent, but not recognition, believed to rely less on the hippocampus. Recall was better for participants that gave higher presence ratings for their experience in the virtual environment. These ratings were higher for the novel compared to the familiar virtual environment, suggesting that novelty increased attention for the virtual rather than real environment; however, this did not explain the effect of novelty on recall.